2017
DOI: 10.1017/s0033291717002033
|View full text |Cite
|
Sign up to set email alerts
|

9/11-related PTSD among highly exposed populations: a systematic review 15 years after the attack

Abstract: Background The 11 September 2001 (9/11) attacks were unprecedented in magnitude and mental health impact. While a large body of research has emerged since the attacks, published reviews are few, and are limited by an emphasis on cross-sectional research, short time frame, and exclusion of treatment studies. Additionally, to date, there has been no systematic review of available longitudinal information as a unique data set. Consequently, knowledge regarding long-term trajectories of 9/11-related post-traumatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
68
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 57 publications
6
68
0
1
Order By: Relevance
“…The total score is calculated by adding together the response values of each item, with higher scores indicating more severe levels of depressive, anxiety, and stress symptoms. The score at the DASS-depression subscale (e.g., "I felt that I had nothing to look forward to") is divided into normal (0-9), mild (10)(11)(12), moderate (13)(14)(15)(16)(17)(18)(19)(20), severe (21)(22)(23)(24)(25)(26)(27), and extremely severe depression (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). The score at the DASS-anxiety subscale (e.g., "I was worried about situations in which I might panic and make a fool of myself") is divided into normal (0-6), mild (7-9), moderate (10)(11)(12)(13)(14), severe (15)(16)(17)(18)(19), and extremely severe anxiety .…”
Section: Assessment Toolsmentioning
confidence: 99%
See 2 more Smart Citations
“…The total score is calculated by adding together the response values of each item, with higher scores indicating more severe levels of depressive, anxiety, and stress symptoms. The score at the DASS-depression subscale (e.g., "I felt that I had nothing to look forward to") is divided into normal (0-9), mild (10)(11)(12), moderate (13)(14)(15)(16)(17)(18)(19)(20), severe (21)(22)(23)(24)(25)(26)(27), and extremely severe depression (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). The score at the DASS-anxiety subscale (e.g., "I was worried about situations in which I might panic and make a fool of myself") is divided into normal (0-6), mild (7-9), moderate (10)(11)(12)(13)(14), severe (15)(16)(17)(18)(19), and extremely severe anxiety .…”
Section: Assessment Toolsmentioning
confidence: 99%
“…The score at the DASS-anxiety subscale (e.g., "I was worried about situations in which I might panic and make a fool of myself") is divided into normal (0-6), mild (7-9), moderate (10)(11)(12)(13)(14), severe (15)(16)(17)(18)(19), and extremely severe anxiety . The score at the DASS-stress subscale (e.g., "I tended to over-react to situations") is divided into normal (0-10), mild (11)(12)(13)(14)(15)(16)(17)(18), moderate (19)(20)(21)(22)(23)(24)(25)(26), severe (27-34), and extremely severe stress (35)(36)(37)(38)(39)(40)(41)(42).…”
Section: Assessment Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14] Among those exposed to the World Trade Center (WTC) attacks in New York, New York, on (9/11), the estimated prevalence of probable PTSD ranges from 3.8% to 29.6%, depending on the population. 15 In a recent mortality study among enrollees of the WTC Health Registry (Registry), standardized mortality ratios for suicide were significantly elevated among responders vs the reference population. 16 In previous mortality studies among Registry enrollees, inconclusive findings on the association between exposure to 9/11 and mortality were observed, 16,17 potentially owing to insufficient follow-up time.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to disasters might pose a direct threat to individuals' mental health (Cheng, Liang, Fu, & Liu, 2018;Lai, Lewis, Livings, La Greca, & Esnard, 2017). Among psychopathologies, posttraumatic stress disorder (PTSD) is one of the highest-concern and commonly studied disorders that can develop following disasters because it is directly related to traumatic events (Lowell et al, 2018). Previous research has identified a range of distinct trajectories of PTSD following natural disasters, which indicates that the course of PTSD is heterogeneous among populations (Galatzer-Levy, Huang, & Bonanno, 2018;Weems & Graham, 2014).…”
Section: Introductionmentioning
confidence: 99%